Effects of steam dilution on laminar flame speeds of H2/air/H2O mixtures at atmospheric and elevated pressures. (12th April 2018) - Lyu, Yajin; Qiu, Penghua; Liu, Li; Yang, Chenchen; Sun, Shaozeng
Abstract: The laminar flame speeds of H2 /air with steam dilution (up to 33 vol%) were measured over a wide range of equivalence ratio (0.9–3.0) at atmospheric and elevated pressures (up to 5 atm) by an improved Bunsen burner method. Burke, Sun, HP (High Pressure H2 /O2 mechanism), and Davis mechanisms were employed to calculate the laminar flame speeds and analyze different effects of steam addition. Four studied mechanisms all underestimated the laminar flame speeds of H2 /air/H2 O mixtures at medium equivalence ratios while the Burke mechanism provided the best estimates. When the steam concentration was lower than 12%, increasing pressure first increased and then decreased the laminar flame speed, the inflection point appeared at 2.5 atm. When the steam concentration was greater than 12%, increasing the pressure monotonously decrease the laminar flame speed. The chemical effect was amplified by elevated pressure and it played an important role for the inhibiting effect of the pressure on laminar flame speed. The fluctuations of the chemical effect at 1 atm were mainly caused by three-body reactions, while the turn at 5 atm was mainly caused by the direct reaction effect. Elevated pressure and steam addition amplified the influences of uncertainties in the rate constants for elementary reactions, which might leaded to the disagreement between experimental and simulation results. Highlights: Laminar flame speeds of H2 /air/H2 O mixtures were studied under elevated pressures. Among the four reaction mechanisms tested, Burke-Mech provides the best estimates. The relationship between laminar flame speed and pressure changed with H2 O content. Three-body effect is the main reason for fluctuations of chemical effect at 1 atm. Direct reaction effect causes the turn of chemical effect at 5 atm.